Proposta de framework para escutas populares através de mapas colaborativos - Oliveira, Renata da Silva (2019)
The present research investigated the implementation of improvements in computational platforms that promote actions of popular hearing based on crowdsourcing, specifically in collaborative maps. Although some studies show strong evidence that they simplify communication between the various social actors and the public power, with an economic and rapid approach, it was observed that some cases still present a low level of engagement and transparency, which is contradictory with crowdsourcing principles. It turned out that, probably due to the still-existing top-down approach, such initiatives still do not represent a real community-generated organization movement. And, similar to traditional models, they still have exogenous ideas implanted or in test by technicians, urban planner or members of academic community. In this way, a line of action was drawn to systematize good practices for the development of new popular participation platforms that rely on collaborative maps. The intention was to list possible improvements that, besides providing autonomy to the organizers and stakeholders, should include a stage of shared diagnosis of the problem under discussion, built by the community in an assisted and streamlined way. The approach researched ways to virtually recreate the methodologies adopted in face-to-face community planning workshops such as the MIT CAP as well as Sustainable Urbanism. These results were compiled in the form of a framework, intended to assist the development and prototyping of the task flow analysis and of the user interface of popular hearing platforms. To this end, the framework is intended to help developers build this type of platform in the future. Through the Unified Modeling Language (UML), it sought to organize a common line for such solutions, incorporating steps already enshrined in the conventional models of popular tapping. Making available a preliminary indication as a suggestion for a systems business modeling, in which it is possible to understand the business overview, business use case diagrams, activity diagram, among others. Finally, good practices and tools were compiled to promote transparency and engagement in popular hearing initiatives.